Inventory Control Analysis of Sticker Raw Materials Using Continuous (Q) and Periodic Review (P) Methods at PT Adiguna Label Indonesia - Pratama, Ivan Alvino; Ernawati, Dira (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT Adiguna Label Indonesia is one of the manufacturing industries engaged in producing label stickers. To produce label stickers, this company requires the main raw material, one of which is substrate. PT Adiguna Label Indonesia is presently having trouble managing the supply of substrate type Raflacoat 22.5 cm. This type of substrate often fluctuates in the amount of demand, so it is not uncommon to experience stockouts that cause many customers to cancel orders due to insufficient material supplies. To reduce the susceptibility to out-of-stock and overstock situations along with the overall cost of inventory at PT Adiguna Label Indonesia, this study intends to manage the inventory of raflacoat substrate 22.5 cm. The method used is Continuous Review (Q) Lost Sales and Periodic Review (P) Lost Sales. The calculation results obtained that the total cost of minimal inventory is the method of Continuous Review (Q) Lost Sales of IDR. 2,160,302,178 with the company method of IDR.2,326,322,927, resulting in cost savings of IDR. 166.020.750.- or 7.14%. After forecasting in March 2023 – February 2025, the total need reached 2304 rolls, then the inventory control of Raflacoat 22.5cm substrate raw materials obtained a number of orders of 193 rolls / one order with a total inventory cost of IDR. 2,739,423,128,-.